Comparative genomic hybridization shows complex genomic changes of plasmacytoid urothelial carcinoma - Keck, Bastian; Elhnann, Christina; Stoehr, Robert; Weigelt, Katrin; Goebell, Peter; Kunath, Frank; Taubert, Helge; Hartmann, Arndt; Wullich, Bernd; Wach, Sven (Urologic Oncology-Seminars and Original Investigations, 2014)
To describe genomic imbalances in plasmacytoid urothelial carcinoma (PUC), which is a rare and aggressive variant of urothelial carcinoma (UC).In total, 25 formalin-fixed paraffin-embedded PUCs were analyzed by metaphase comparative genomic hybridization. Genomic imbalances were considered to be characteristic if they were detected in >= 20% of the cases. Chromosome regions deviating by >= 3 standard deviations from the average chromosome profile were scored as chromosomal gains or losses. Copy-number variations (CNVs) of CDH1 (16q 22.1), SNAI1 (20q 13.1), CCND1 (11q13.3), ERBB2 (17q12), and FOXO3 (6q21) were validated using quantitative polymerase chain reaction.Chromosomal aberrations were detected in every PUC analyzed, and the average number of aberrations was 10.24 (ranging from 1-15). Characteristic aberrations were gains on 1q (48%), 3p (20%), 6p (32%), 11q (72%), 15q (36%), 16q (44%), 17p (76%), 17q (88%), and 20q (88%) and losses on 2q (24%) 4p (36%), 4q (84%), 5q (44%), 6q (68%), 13q (20%), and Xq (52%). polymerase chain reaction-based analysis of CNV for CCND1 (11q13) showed a deletion in 73% of the cases. CDH1 (16q22) was deleted in 72% and amplified in 5%. ERBB2 (17q12) displayed remarkably few copy-number alterations, with only 14% showing an amplification. SNAI1 (20q13) showed reduced gene copy numbers in 59.1% of the cases, whereas no copy-number gains were detected. FOXO3 (6q21) exhibited the lowest number of copy-number alterations, with 9% of all cases showing an amplification.In PUCs, the frequency of aneuploidy and the complexity of genomic changes per tumor are greater than those described in conventional UC. The aberrations described in PUC involve the same regions that are associated with aggressive biological behavior in conventional UC. Gains on 11q, 17q, 17p, and 20q and losses on 4q and 6q affect most PUCs and seem to harbor important chromosomal regions for PUC carcinogenesis. Large-scale deletions on chromosome 9 were not detected. CNV analysis indicates heterozygous deletion of CDH1 as one underlying mechanism of loss of membranous E-cadherin in PUC. Loss of CCND1 and SNAI1 is a common molecular feature and could contribute to the aggressive biological behavior of PUC.
EVALuna2:6676